Protecting Children from Harmful Digital Content: Legal Responsibilities in Makassar Family Karaoke - Salmi Salmi; Abdul Rahman Nur; Sulastryani Sulastryani; Dandi Darmadi (Faculty of Law Universitas Jenderal Soedirman, 2025)
This research analyzes the legal responsibility of family singing house business actors toward minor consumers in the context of digital content transformation in Makassar City. Family singing homes as a fast-growing entertainment industry face significant challenges regarding the protection of child consumers from digital content that contains pornographic elements. This research identifies the gap between legal provisions and practical implementation in the field through a juridical-empirical approach with a case study method. The results show that digital content transformation in family singing homes has changed the character, accessibility, and potential impact of content on child consumers. In business practices, it was found that there was an absence of a content filtering system, access restrictions based on age, and supervision of the activities of child consumers. The main obstacles in implementing the legal responsibilities of business actors include regulatory, technical, economic, and sociocultural aspects. This research proposes an alternative model of child consumer protection that integrates co-regulation, technological solutions, community governance, and diversified liability. The study's novelty lies in analyzing the multi-disciplinary intersection of law, the empirical exploration of digital content transformation, developing alternative models of child consumer protection, and contextualizing consumer protection law in local wisdom. The findings of this research have implications for reforming digital entertainment industry regulations, developing best practices, and consumer education and empowerment to ensure adequate protection for child consumers in the digital transformation era